Strategi Pemulihan Potensi Pariwisata Di Kota Surakarta - Made Prasta (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2022)
The purpose of this paper are; 1) Analyze the tourism potential in Surakarta City, 2) Analyze the condition of the tourism sector in Surakarta City, 3) To find how the strategies carried out by the Surakarta city government to restore Surakarta potential tourismt. Library research is used in this paper with a qualitative descriptive analysis approach. The results of the study show the mayority potential tourism in Surakarta are cultural tourism and nature reserves. Covid-19 pandemic desease in Surakarta represent a tourist visitor decrease. The strategy carried out by the government through Dinas Pariwisata is to hold competitions and events online. Some tourism objects are still open with operating hours that have been determined in the Surat Edaran from Surakarta Mayor number: 067/1869 dated June 14, 2021. This paper proposes that, such competitions and events should continue and be added by using virtual tours. The author recommends further research in making the right strategy to promote tourism in the city of Surakarta.